The Image of Group Fitness Instructors: An Intra- and Inter-Country Comparison Between Portugal and Romania - Viorel Petru Ardelean; Vlad Adrian Geantă; Corina Dulceanu; Claudiu Bulzan; Sónia Brito-Costa; Guilherme Eustáquio Furtado; Ricardo Gomes; Fernando Martins; Francisco Campos (Behavioral Sciences)
Fitness instructors play an essential role in fitness services, as they require both technical and interpersonal skills. A good image of a fitness instructor can be defined as having a pleasant appearance and good presentation in terms of hygiene and/or clothing used, which is appropriate for the context and characteristics of the participants. Their image significantly influences participants’ perceptions and satisfaction. The objective of this study was to conduct a comparative analysis between Romania and Portugal regarding the quality of services offered within group fitness classes, focusing on instructors. It involved 133 group fitness instructors and 210 participants from Romania and Portugal. An adaptation of the Szumilewicz questionnaire was used to assess the importance of the different attributes of the fitness instructor’s image. Statistical analyses included descriptive statistics, t-tests, and effect size to compare perceptions between countries and groups. Romanian instructors and participants generally attributed more importance to the fitness instructor’s image compared to their Portuguese counterparts. Significant differences were found in attributes like physical fitness, technical execution, and communication. Instructors tended to overestimate the importance of their image compared to participants. The fitness instructor’s image is crucial in determining participant satisfaction and the perceptions of service quality. The innovative aspect of this study lies in its intercultural comparison, which highlights how cultural context influences the perception of a fitness instructor’s attributes, such as physical fitness, technical execution, and communication. The practical application of these findings lies in the suggestion that fitness professionals should tailor their approach, balancing technical skills and interpersonal communication to align with the cultural expectations of their participants. This culturally sensitive approach is essential for enhancing participant satisfaction and improving the overall quality of fitness services.